2020
DOI: 10.35808/ersj/1864
|View full text |Cite
|
Sign up to set email alerts
|

Economic Sustainability of Dairy Farms in the EU

Abstract: Purpose: The objective of this research is to evaluate changes in the economic sustainability of dairy farms in the European Union (EU) countries during 2007-2016 when dairy quotas were being removed in the EU. We wanted to answer the question what is the economic sustainability of dairy farms in the EU, and how has the economic sustainability in the EU countries changed after the accession of new member states in 2004 and 2017. Design/Approach/Methodology: An economic sustainability assessment of farms was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It underscored the need for a comprehensive approach to sustainability that encompasses multiple dimensions [26]. Bórawski et al (2020) focused on the economic sustainability of dairy farms in the European Union (EU). Their research highlighted the significance of production efficiency and adherence to environmental regulations in achieving sustainability in modern dairy farming.…”
Section: Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…It underscored the need for a comprehensive approach to sustainability that encompasses multiple dimensions [26]. Bórawski et al (2020) focused on the economic sustainability of dairy farms in the European Union (EU). Their research highlighted the significance of production efficiency and adherence to environmental regulations in achieving sustainability in modern dairy farming.…”
Section: Farmingmentioning
confidence: 99%
“…Their research highlighted the significance of production efficiency and adherence to environmental regulations in achieving sustainability in modern dairy farming. The study emphasized the importance of economic sustainability assessments to complement existing literature on efficiency and environmental aspects [27]. Alem (2021) explored the role of technical efficiency in sustainable development within Norwegian dairy farms.…”
Section: Farmingmentioning
confidence: 99%
“…The issue of sustainability of farms in the EU (European Union) has been measured by different authors. Bórawski et al [37] measured the economic sustainability of dairy farms. They found that the highest economic sustainability had been achieved by farms in the Czech Republic, Denmark, Slovakia and Sweden.…”
Section: Sustainable Agriculture As a Development Paradigmmentioning
confidence: 99%
“…Performance evaluation has become a significant topic in supply chain management [12], including the dairy sector. Although a number of studies have been conducted on economic sustainability at the farm level (e.g., [14][15][16][17]), the discussion cannot be limited to this initial link of the dairy supply chain. Given that milk is a perishable commodity that cannot be stored in its raw form, its processing and transformation are crucial in the dairy sector [18].…”
Section: Introductionmentioning
confidence: 99%